Pengaruh Persyaratan Kredit dan Metode Penagihan Terhadap Kemampuan Bayar Debitur di PT Clipan Finance Cabang Sukabumi - Aulia Ananda, Cindy; Sudarma, Ade (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the influence of credit requirements and collection methods on the repayment ability of debtors at PT Clipan Finance Sukabumi Branch. The search employed a quantitative method with a survey approach. Data were collected through questionnaires distributed a 92 respondents who are active debtors of the company. The data were analyzed using multiple linear regression. The result show that both credit requirements and collection methods have a positive and significant effect, both partially and simultaneously, on the repayment ability of debtors. This findings indicate that proper credit evaluation and effective collection strategies can improve debtor compliance in fulfilling financing obligations.